Effects of coffee and tea consumption on urinary incontinence in female twins - Tettamanti, G (2011)
OBJECTIVES: To assess the effect of coffee and tea consumption on symptoms of urinary incontinence. DESIGN: Population based study SETTING: The Swedish Twin Register POPULATION: In 2005, all twins born between 1959–1985 in Sweden (n = 42 852) were invited to participate in a web-based survey to screen for common complex diseases and common exposures. The present study was limited to female twins with information about at least one urinary symptoms and coffee and tea consumption (n = 14 031). MAIN OUTCOME MEASURE: The association between coffe and tea consumption and urinary incontinence, as well as, nocturia was estimated as odds ratios (ORs) with 95% confidence intervals (CIs). RESULTS: Women with a high coffee intake were at lower risk of any urinary incontinence (OR 0.78, 95% confidence intervals (CI) 0.64-0.98) compared to women not drinking coffee. Coffee intake and incontinence subtypes showed no significant associations whereas high tea consumption was specifically associated with a risk for overactive bladder (OR 1.34, 95% CI 11.07-1.67) and nocturia (OR 1.18, 95% CI 1.01-1.38). Results from co-twin control analysis suggested that the associations observed in logistic regression were mainly due to familial effects. CONCLUSIONS: This study suggests that coffee and tea consumption has a limited effect on urinary incontinence symptoms. Familial and genetic effects may have confounded the associations observed in previous studies.